The isotopic composition of carbon and oxygen of the calcite of veinlet-impregnated mineralization of rock complexes of the north-western part of the Krosno zone of the Ukrainian Carpathians - Naumko, I.М.; Ponomarenko, О.М.; Zankovych, H. О.; Моrоz, V. S.; Proskurko, L. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
The isotopic composition of carbon and oxygen of the calcite of veinlet-impregnated mineralization of terrigenous rock complexes of geological structures of the north-western part of the Krosno zone of the Ukrainian Carpathians is established. Sufficiently homogeneous values of δ 13C (−2.53…−0.29‰, standard PDB), and δ 18O (22.57…26.52‰, standard SMOW) have revealed. They are not correlated with a depth of the occurrence and a spatial distribution of veinlets in natural denudations, the composition and the age of the enclosing rock, etc. The proximity of these values to those of the calcite of the veinlet-impregnated mineralization and enclosing rocks within the limits of the Lopushna and Kokhanivka oil fields in allochthonous and autochthonous complexes of the Ciscarpathia suggests a similarity of the processes of transfer of hydrocarbons by migrating fluids and the healing of migration fractures with a mineral matter as a result of the intensification of vertical migration phenomena, and, therefore, the possibility of the formation of hydrocarbon deposits in paraautochthonous sediments of the flish Paleogene in the so-called zones of tight collectors.